Increased miR-155 in Microglial Exosomes Following Heat Stress Accelerates Neuronal Autophagy via Their Transfer Into Neurons - Li, Ping; Luo, Xue; Luo, Zhen; He, Gen-Lin; Shen, Ting-Ting; Yu, Xue-Ting; Wang, Ze-Ze; Tan, Yu-Long; Liu, Xiao-Qian; Yang, Xue-Sen (Frontiers in Cellular Neuroscience, 2022)
Background: Heat stroke is the outcome of excessive heat stress, which results in core temperatures exceeding 40°C accompanied by a series of complications. The brain is particularly vulnerable to damage from heat stress. In our previous studies, both activated microglia and increased neuronal autophagy were found in the cortices of mice with heat stroke. However, whether activated microglia can accelerate neuronal autophagy under heat stress conditions is still unknown. In this study, we aimed to investigate the underlying mechanism that caused neuronal autophagy upregulation in heat stroke from the perspective of exosome-mediated intercellular communication. Methods: In this study, BV2 and N2a cells were used instead of microglia and neurons, respectively. Exosomes were extracted from BV2 culture supernatants by ultracentrifugation and then characterized via transmission electron microscopy, nanoparticle tracking analysis and Western blotting. N2a cells pretreated with/without miR-155 inhibitor were cocultured with microglial exosomes that were treated with/without heat stress or miR-155 overexpression and subsequently subjected to heat stress treatment. Autophagy in N2a cells was assessed by detecting autophagosomes and autophagy-related proteins through transmission electron microscopy, immunofluorescence and Western blotting. The expression of miR-155 in BV2 and BV2 exosomes and N2a cells was measured using real-time reverse transcription polymerase chain reaction. Target binding analysis was verified via a dual-luciferase reporter assay. Results: N2a autophagy moderately increased in response to heat stress and accelerated by BV2 cells through transferring exosomes to neurons. Furthermore, we found that neuronal autophagy was positively correlated with the content of miR-155 in microglial exosomes. Inhibition of miR-155 partly abolished autophagy in N2a cells, which was increased by coculture with miR-155-upregulated exosomes. Mechanistic analysis confirmed that Rheb is a functional target of miR-155 and that microglial exosomal miR-155 accelerated heat stress-induced neuronal autophagy mainly by regulating the Rheb-mTOR signaling pathway.